Аrmenian delegations and the problem of patronage of Аrmenia - Manukyan, Larisa (History and Culture, 2025)
On November 11th 1918, after the end of World War I, the world continued to be complex, full of many contradictions and unresolved issues. The victory of the Allied Entente states in the World War gave the right to sign peace treaties with the losing side and to resolve all political issues after the end of the war. For that purpose on January 18th 1919 the big states called a special conference in Paris (Versailles), which continued intermittently until January 21st 1920. In 1919, by the decision of the Paris Peace Conference, a special organization, the League of Nations, was created in order to maintain international peace and develop cooperation between nations. It was adapted to the political aspirations of the big states, “from the very beginning it created injustice and inequality”. The organization established a system of administrative management (patronage), which was to be applied to Armenia as well. The Armenian state, formed as a result of the disintegration of Ottoman Turkey, had to benefit from the protection of the state that took the patronage (mandate) under the supervision of the League of Nations. Armenia was not officially invited to the Paris Peace Conference because it was not recognized as a warring party. But during the preparation of the peace treaty with Turkey by the great powers, in connection with the discussion and solution of the Armenian question, two Armenian delegations were in Paris, delegation of the Republic of Armenia headed by Avetis Aharonyan and National delegation headed by Boghos Nubar Pasha. The delegations were actively engaged in many problems related to the Armenian issue. The question was which state was interested in taking over Armenia’s patronage in that difficult historical period. On the other hand, it was extremely important that the patronage of which great state the representatives of our delegations, the RA government, Western Armenians, public, political, and national figures would prefer, and whether it was possible to implement it or not. In 1919, the League of Nations discussed and decided to hand over the mandate of Armenia to the United States. In 1918 after the declaration (in our opinion) Armenia was looking for the patronage of a powerful state, a mandate. Eventually no state wanted to take over the patronage of Armenia.